Alleviation of Cadmium Stress by Silicon Supplementation in Peas by the Modulation of Morpho-Physio-Biochemical Variables and Health Risk Assessment - Tahira Batool; Sabiha Javied; Kamran Ashraf; Khawar Sultan; Qamar uz Zaman; Fasih Ullah Haider (Life, 2022)
Agricultural soil quality degradation by potentially toxic elements, specifically cadmium (Cd), poses a significant threat to plant growth and the health of humans. However, the supplementation of various salts of silicon (Si) to mitigate the adverse effect of Cd on the productivity of peas (Pisum sativum L.) is less known. Therefore, the present investigation was designed to evaluate the exogenous application at various levels (0, 0.50, 1.00 and 1.50 mM) of silicate compounds (sodium and potassium silicates) on pea growth, gaseous exchange, antioxidant enzyme activities and the potential health risk of Cd stress (20 mg kg−1 of soil) using CdCl2. The findings of the study showed that Cd stress significantly reduced growth, the fresh and dry biomass of roots and shoots and chlorophyll content. In addition, electrolyte leakage, antioxidant enzymes and the content of Cd in plant tissues were enhanced in Cd-induced stressed plants. An application of Si enhanced the development of stressed plants by modulating the growth of fresh and dry biomass, improving the chlorophyll contents and decreasing leakage from the plasma membrane. Furthermore, Si addition performed a vital function in relieving the effects of Cd stress by stimulating antioxidant potential. Hence, a significant level of metal protection was achieved by 1.00 mM of potassium silicate application under the Cd levels related to stress conditions, pointing to the fact that the Si concentration required for plant growth under Cd stress surpassed that which was required for general growth, enzymatic antioxidants regulation and limiting toxic metal uptake in plant tissues under normal conditions. The findings of this research work provide a feasible approach to reduce Cd toxicity in peas and to manage the entry and accumulation of Cd in food crops.